Clementine : Friend of the Week - Pennypacker, Sara, 1951-; Frazee, Marla (London : Hodder Children's Books, 2010)
With her kitten, Moisturizer, missing and having fought with her best friend, Margaret, eight-year-old Clementine finds it hard to concentrate on doing her best as her classmate's Friend of the Week.
4.2
3-6.
3-6
Keywords: Cats -- Juvenile fiction; Families -- Massachusetts -- Juvenile fiction; Friendship -- Juvenile fiction; Lost articles -- Juvenile fiction; Schools -- Juvenile fiction; Cats -- Fiction; Family life -- Massachusetts -- Fiction; Friendship -- Fiction; Humorous stories; Lost and found possessions -- Fiction; Schools -- Fiction; Cats -- Fiction; Family life -- Massachusetts -- Fiction; Friendship -- Fiction; Humorous fiction; Lost and found possessions -- Fiction; School stories; Boston (Mass.) -- Juvenile fiction; Boston (Mass.) -- Fiction; Boston (Mass.) -- Fiction; Humorous fiction